"Mission as disciple-making" Scripture Union's discipleship and leadership development approaches in senior high schools in Kumasi - Awuah-Gyawu, Daniel (Missionalia, 2025)
Despite Scripture Union's (SU) significant role in fostering Christian growth and nurturing leadership qualities among students, scholarly literature on the group's methodologies and impacts is notably sparse. This article explores SU's leadership development and discipleship approach among senior high school students in the Kumasi Metropolis of Ghana. This research uses data from interviews, institutional records, and participant observation, and focuses on how SU blends traditional and contemporary strategies towards meeting the discipleship and leadership development needs of young ones in the Kumasi Metropolis of Ghana. While SU effectively engages students and fosters a nurturing environment, challenges remain in the availability of devotional materials, follow-up of new converts, and overreliance on external support and offline approaches. The study sheds light on the strengths and areas of growth within SU's discipleship initiatives, offering valuable insights for ongoing refinement and enhancement